Fires in GunaiKurnai Country Landscape Fires and their Impacts on Aboriginal Cultural Heritage Places and Artefacts in Southeastern Australia - Buettel, Jessie; David, Bruno (2023)
Anthropogenic climate change has become a reality, and in Australia this means longer wildfire seasons with more intense fires across a wider area. The GunaiKurnai people of southeastern Victoria saw a large proportion of their Country decimated by the Gippsland Fires of 'Black Summer' (2019-2020), prompting questions about the management of Country and its heritage places and artefacts, and of the role that traditional ('cultural') burning could play. This volume, written at the request of the GunaiKurnai Land and Waters Aboriginal Corporation (GKLaWAC), seeks to investigate these twin issues. Bringing together a multi-disciplinary team of Aboriginal Elders, archaeologists, environmental scientists, ecologists, historians and art historians, it considers the histories of GunaiKurnai and European settler burning-based landscape management practices, the impacts of fire on specific classes of cultural materials, and the broader impact of changing wildfire patterns on cultural sites in the landscape. This is a truly collaborative venture that sees GunaiKurnai and academic expertise brought to bear in the service of common and pressing issues.